Abatacept and its use in the treatment of rheumatoid arthritis (RA) in the Czech Republic-data from the ATTRA registry - Horák, Pavel; Skácelová, Martina; Hejduk, Karel; Smržová, Andrea; Pavelka, Karel (Clinical rheumatology, 2013)
The Czech national registry ATTRA collects data from patients with rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, and juvenile idiopathic arthritis, treated with the biologic drugs. ATTRA is a prospective centralized computerized registry of patients with a focus on efficacy, safety, and quality of life data. Abatacept is approved as a second-line agent which can be prescribed after a failure of at least one TNF-alfa inhibitor. Data of patients treated with abatacept has been collected since 2008. A statistical analysis of the group of RA patients treated with abatacept was performed recently. ATTRA registered 162 patients with RA treated with abatacept, the mean age 51.0 ± 12.2 (median 53.1, 19-74 years), the mean duration of the disease was 14 ± 9.1, median 11.3 years (0-41). One hundred thirty patients (80.2 %) were female. The mean DAS28 was at week 0, 5.9 ± 1.1, at week 16, 4.1 ± 1.4, at week 24, 3.8 ± 1.2, at week 36, 3.6 ± 1.3, and at week 52, 3.5 ± 1.2. DAS28 remission was achieved at week 16 in 15.8 %, at week 24 in 10 %, at week 36 in 20.9 %, and at week 2 in 20.8 % of patients. Of those patients with a DAS28 <2.6 (remission) at week 16, 58.3 % remained in remission at the week 52. Of those patients with DAS28 >5.1 (high disease activity) at the week 16, only 41.7 % had DAS >5.1 at week 52. One year on treatment survival was 82 %. Altogether 50 non-serious adverse events (AE) were reported in 36 patients (22 %) and 11 serious AE in 10 patients (6 %) with the most common being infections (31) and skin rashes (5). Just one non-serious allergic reaction was reported. Data from the ATTRA registry confirms a good overall efficacy and safety profile and a very good on drug survival with abatacept.
Keywords: Patient Safety; senioři; psoriatická artritida; biologické přípravky; Abatacept; abatacept; Arthritis, Psoriatic; Time Factors; Remission Induction; bezpečnost pacientů; Česká republika; juvenilní artritida; výsledek terapie; Middle Aged; registrace; mužské pohlaví; Adult; mladý dospělý; Czech Republic; Registries; kvalita života; ankylózující spondylitida; Arthritis, Juvenile; Young Adult; ženské pohlaví; Spondylitis, Ankylosing; Humans; antirevmatika; Arthritis, Rheumatoid; časové faktory; lidé středního věku; Immunoconjugates; indukce remise; revmatoidní artritida; Antirheumatic Agents; dospělí; imunokonjugáty; Biological Products; Female; Aged; Quality of Life; Treatment Outcome; lidé; Male